What are Sustainable Forests? - Shah, S. A. (Indian Forester, 1999)
Forests of India were and still are, largely managed for Sustained Yield of industrial timber assuming that sustainability of timber yield would be achieved. (Little difference was, however, perceived between Sustainable Yield of timber and Sustainable Forests). In practice, this did not happen. If Sustainable Yield does not mean Sustainable Forests then, what are these Sustainable Forests? Little is known, much less is documented about the numerous attributes of such forests. Hence this effort based on the author's field observations spanning about three decades. Sustainable Forest Ecosystems have several dimensions and sub-systems; Timber Production is just one ofthem. They are so much interwoven that if you touch one, you touch all. It is conceptualized that Sustainable Forests are environmentally sound, ecologically stable, healthy and supportive of all life forms which inhabit them; also, concomitantly, sustain forest dependent communities. It is argued that, Sustainable Forests cannot exist without Sustainable Communities. Also, if a part of a given forest ecosystem, say a village forest, is not sustainable, then the whole forest ecosystem cannot be sustainable. Sustainable Forest is a self-propelling, self-sustaining, self-fertilizing and self-regenerating machine designed by Mother Nature. It is a multi-species, multi-layered and all-aged crop. Its composition, architecture and alignment of various species within and between various layers is such that, it uses solar energy optimally at different levels as well as uses soil fertility optimally at different depths. In view of this, the biomass production is optimum, other things remaining the same. Sustainable Forests imply environmentally sound Logging, Harvesting, Transporting, Processing and Consumption.